Authentic Materials For Teaching Writing: A Critical Look - Setyowati, Lestari - (Universitas Negeri Makassar, 2019)
Teaching writing is not easy. Writing teachers often face problems with what kind of materials suitable for the students. This paper is intended to describe 1) the theoretical relationship between Content-Based Instruction and authentic materials that can be used by language teachers to teach writing in the classroom, 2) the previous studies of authentic materials used for teaching writing, 3) the type of authentic materials which can be used for teaching writing, and 4) the advantages and disadvantages of using authentic materials for teaching writing. The method used was qualitative research focused on content analysis. The instrument used was mainly human instrument and documentation. The result of the extensive review of literature shows that 1) one of the main feature of content-based instruction is the use of authentic materials for teaching; 2) most studies in the area of authentic materials for teaching writing shows the effectiveness of authentic materials for teaching procedure texts, descriptive texts and essay writing; 3) the type of authentic materials used for teaching writing is categorized based on how it is transmitted, namely audio, visual, and printed material materials; 4) aside from having its advantages, authentic materials also give challenges for the teacher to use it for classroom teaching, among others are practicality, comprehensibility and appropriateness.